Toward reliable thalamic segmentation: an evaluation of automated methods for structural MRI - Georgios P. D. Argyropoulos; Christopher R. Butler; Manojkumar Saranathan (Brain Structure and Function, 2026)
Automated thalamic nuclear segmentation has contributed towards a shift in neuroimaging analyses, from treating the thalamus as a homogeneous, passive relay, to a set of individual nuclei, embedded within distinct brain-wide circuits. However, many studies continue to widely rely on FreeSurfer’s segmentation of T1-weighted structural MRIs, despite their poor intrathalamic nuclear contrast. Meanwhile, a convolutional neural network tool has been developed for FreeSurfer, using information from both diffusion and T1-weighted MRIs. Another popular thalamic nuclear segmentation technique is HIPS-THOMAS, a multi-atlas-based method that leverages white-matter-like contrast synthesized from T1-weighted MRIs. However, comparisons amongst methods remain scant, and the thalamic atlases against which these methods have been assessed have their own limitations. These issues may compromise the quality of cross-species comparisons, structural and functional connectivity studies in health and disease, as well as the efficacy of neuromodulatory interventions targeting the thalamus. Here, we report, for the first time, comparisons amongst HIPS-THOMAS, the standard FreeSurfer segmentation, and its more recent development, against two thalamic atlases. We used two cohorts of healthy adults, and one cohort of patients in the chronic phase of autoimmune limbic encephalitis. In healthy adults, HIPS-THOMAS surpassed, not only the standard FreeSurfer segmentation, but also its more recent, diffusion-based update. The improvements made with the latter were limited to a few nuclei. Finally, the standard FreeSurfer method underperformed in distinguishing between patients and healthy controls based on the affected anteroventral and pulvinar nuclei. We provide recommendations on automated segmentation methods of the human thalamus using structural brain imaging.

LC–MS-based phytochemical analysis and drug-likeness prediction of KB yoga: an ayurvedic polyherbal formulation - Vivek Palengara; P. B. Benil; M. Deepak; N. Manojkumar (Vegetos, 2026)

Revolutionizing energy storage: Self-charging supercapacitors toward self-powered micro and nano systems - Kaliyannan Manojkumar; Mukilan Muthuramalingam; Arunmetha Sundamoorthy; P S Srinivasa Babu; Rayavarapu Vamsi; Jananipriya Boominathan; Siddabattula Geetha Sri Priyanka; Sugato Hajra; Swati Panda; Hoe Joon Kim; Deepak Dubal; Venkateswaran Vivekananthan (Chemical Engineering Journal, 2025)

Enhancing Early Seedling Stage Salinity Tolerance in Rice Through Brassinosteroid Priming - Tinu Thomas; K. Manojkumar; P. Saravanane; S. Nadaradjan (Journal of Crop Health, 2025)

Marker-assisted pedigree breeding to enhance resistance against bacterial blight, blast, and tolerance to low soil phosphorus in the Indian elite rice cultivar MTU1121 - Manojkumar Duppala; T. Srinivas; L. V. Subba Rao; Y. Suneetha; R. M. Sundaram; V. Prasannakumari; P. V. Satyanaryana; R. AbdulFiyaz; C. H. Raveendra; Gurjeet Singh (Cereal Research Communications, 2025)

Dietary papaya peel extract ameliorates the crowding stress, enhances growth and immunity in Labeo rohita fingerlings - Atshaya Sundararajan; Narottam P. Sahu; Nazeemashahul Shamna; Manish Jayant; Parimal Sardar; Vasanthakumaran; Naveen S. Krishnamenan; Soumyodeep Bhattacharya; Manojkumar Chandraprakasham; Sangeetha Sankar (Fish Physiology and Biochemistry, 2024)

Robust thalamic nuclei segmentation from T1-weighted MRI using polynomial intensity transformation - Julie P. Vidal; Lola Danet; Patrice Péran; Jérémie Pariente; Meritxell Bach Cuadra; Natalie M. Zahr; Emmanuel J. Barbeau; Manojkumar Saranathan (Brain Structure and Function, 2024)

Sources, occurrence and toxic effects of emerging per- and polyfluoroalkyl substances (PFAS) - Y. Manojkumar; Sridhar Pilli; P. Venkateswara Rao; Rajeshwar Dayal Tyagi (Neurotoxicology and Teratology, 2023)

Effect of physiological and morphological response of Musa acuminata under stress condition with different salinity levels using IoT - P. Manojkumar; A. Dheepanchakkravarthy; P. Senthil Kumar; S. Tamilsevi; C. Srinivasan (International Journal of Environmental Science and Technology, 2022)

Promalabaricone B from Myristica fatua Houtt. seeds demonstrate antidiabetic potential by modulating glucose uptake via the upregulation of AMPK in L6 myotubes - B. Prabha; S. Sini; D. R. Sherin; S. Neethu; K. B. Rameshkumar; T. K. Manojkumar; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Molecular profiling of blast resistance genes and evaluation of leaf and neck blast disease reaction in rice - Haniyambadi B. Manojkumar; Chikkaballi A. Deepak; Kodihally M. Harinikumar; M. P. Rajanna; Belthur Chethana (Journal of Genetics, 2020)

First Record of Arrow Gaper, Champsodon sagittus Nemeth, 1994 (Family: Champsodontidae) from Bay of Bengal, Eastern Indian Ocean - Shikha Rahangdale; Rajan Kumar; K. Kannan; Subal Kumar Roul; L. Ranjith; P. P. Manojkumar (Thalassas: An International Journal of Marine Sciences, 2019)

Morphological Deformities in Neotrygon kuhlii (Muller & Henle, 1841) from Gulf of Mannar, Bay of Bengal, India - L. Ranjith; R. Saravanan; C. Kalidas; M. Kavitha; S. Ramkumar; K. K. Joshi; P. P. Manojkumar (Thalassas: An International Journal of Marine Sciences, 2019)